Intraindividual Comparison of Psychophysical Parameters Between Perimodiolar and Lateral-type Electrode Arrays in Patients With Bilateral Cochlear Implants. Issue 2 (February 2015) - Jeong, Junhui; Kim, Minbum; Heo, Ji Hye; Bang, Mi-Young; Bae, Mi Ran; Kim, Jungmin; Choi, Jae Young
Abstract : Objective: Perimodiolar electrode arrays were developed to improve stimulation of specific neuronal populations and to decrease power consumption; however, they can damage the cochlear structure. We examined and compared psychophysical parameters of perimodiolar and lateral-type electrode arrays in patients who received a different type of bilateral cochlear implant (CI) in each ear. Study Design: Retrospective analysis. Setting: Tertiary referral center. Patients: Eight child patients (three males, five females) received a different CI in each ear (perimodiolar array and lateral array). They received the CIs sequentially (n = 7) or simultaneously (n = 1). Interventions: Diagnostic, therapeutic, and rehabilitative. Main Outcome Measures: Electrically evoked compound action potential, threshold level, comfort level, and dynamic range (DR) of the basal, mid, and apical electrodes were compared. We also surveyed battery consumption for each device. Results: Electrically evoked compound action potential threshold, threshold level, and comfort level were lower for the perimodiolar-type electrode array than for the lateral-type electrode array in most patients. However, the DR for the perimodiolar array was narrower than for the lateral array. For most patients, there was little difference in battery life. Conclusion: Although the level of electrical energy required for auditory stimulation seems to be lower for the perimodiolar electrode array than for the laterally placed array, the DR was wider and the amount of battery consumption was similar. The electrode array should be chosen by considering various patient factors, such as residual hearing.